Pembuatan Sediaan Gel Anti Acne dari Asap Cair Tempurung Kelapa Berbasis Galaktomanan dengan Bakteri Staphylococcus aureus - Nilsya Febrika Zebua; Rahma Yulia; Nia Zulkarnain (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Liquid smoke is a condensate liquid resulting from coconut shell pyrolysis which contains the main constituents of acids, phenols and carbonyls, so it is widely applied as a natural preservative in food and as an anti-bacterial. Gel preparations are preferred because when used they leave a translucent, elastic layer, good drug release and an attractive appearance. This study aims to determine whether liquid smoke can be formulated into an acne gel dosage form on a galactomannan basis which at certain concentrations has antimicrobial activity againstStaphylococcus aureus and does not cause skin irritation. This research was conducted using experimental and descriptive methods. Beginning with collecting literature information related to the content of liquid smoke from coconut shells, then making a galactomannan base, formulation of acne gel preparations from liquid smoke, making microbiological media, methods of testing antimicrobial activity, examining the physical quality of preparations including preparation homogeneity, testing the preparation's pH, testing preparation stability, and irritation test on volunteers. Based on the results of the study, it was shown that liquid smoke can be formulated into an acne gel dosage form based on galactomannan. Homogeneity test results on gel preparations remained homogeneous, the pH obtained remained stable, skin irritation test results did not cause irritation, preparation viscosity test results obtained between 4520-9990 mPas, gel preparation test on growthStaphylococcus aureus at a concentration of 5% gives an inhibition of 15.3 mm and the results of the antibacterial activity test on liquid smoke can inhibit growthStaphylococcus aureus in the minimum range of 12.5 mg/ml gives an inhibitory diameter of 7.0 mm which is included in the medium category.